Global Crises and the Crisis of Global Leadership - Gill, Stephen (Cambridge University Press, 2011)
This groundbreaking collection on global leadership features innovative and critical perspectives by scholars from international relations, political economy, medicine, law and philosophy, from North and South. The book's novel theorization of global leadership is situated historically within the classics of modern political theory and sociology, relating it to the crisis of global capitalism today. Contributors reflect on the multiple political, economic, social, ecological and ethical crises that constitute our current global predicament. The book suggests that there is an overarching condition of global organic crisis, which shapes the political and organizational responses of the dominant global leadership and of various subaltern forces. Contributors argue that to meaningfully address the challenges of the global crisis will require far more effective, inclusive and legitimate forms of global leadership and global governance than have characterized the neoliberal era.